(untitled) (International Journal of Food and Nutritional Sciences, 2021)
The purpose of this study is to examine the anthropometric profiles and physical fitness attributes of female hockey players in Northern India, with a focus on the positions of offensive and defensive. Convenience selection, a method used in many North Indian universities, produced a total of (N=50) female hockey players. These players are divided into two positions offensive (n1=25) and defensive (n2=25). The participants were split up into multiple playing status groups, with ages ranging from 18 to 25. Physical fitness attributes including speed, agility and shoulder strength, and anthropometric measurements like the circumference of the thigh, mid-upper arm, and calf were measured using conventional equipment. After collecting the data, statistical techniques such as descriptive statistics and ‘t’-test were utilized to analyze the data. When analyzing the physical fitness variables, the results showed that the offensive female hockey players demonstrate significantly higher levels in speed (‘t’ =2.34, sig. 0.02) and insignificantly higher in agility (‘t’ =1.13, sig. 0.26) as compared to defensive female hockey players. Further in the case of shoulder strength (‘t’ =0.38, sig. 0.70) defensive female hockey players insignificantly higher as compared to offensive female hockey players. In the case of anthropometric variables, the results of the present study revealed that defensive female hockey players are significantly higher only for their calf circumference (‘t’ =2.69, sig. 0.01) and insignificantly higher for their thigh circumference (‘t’ =0.83, sig. 0.41) and mid upper arm circumference (‘t’ =1.63, sig. 0.11) as compared to offensive female hockey players.